PEMANFAATAN BAGASE TEBU DAN LIMBAH NANAS SEBAGAI BAHAN BAKU PENGHASIL BIOGAS - Hariyadi Hariyadi; Tri Retno Dyah Larasati; Siswanto Siswanto (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2012)
Sugarcane bagasse and pineapple waste were selected as agricultural wastes, by the process of anaerobic fermentation, as well as to study the effect of addition of cow dung, on gas production from sugarcane bagasse, pineapple waste and both blendings. The batch experiment was carried out to use as substrat in 20 L digester for nine treatment of sugarcane bagasse (Bg), pineapple waste (Ns), both blendings (BNs). Completely Randomized experiment method used at the laboratory scale, which intend to found the best combination between Bg-25; Bg-30; Bg-35; Ns-25; Ns-30; Ns-35; BNs-25; BNs-30 and BNs-35. The result showed that during 48 anaerobic fermentation days, the high biogas production of Ns-35; BNs-30 and BNs-35 were 17,2 L; 12,6 L and 12,3 L, respectively. The parameter of TS, VS and COD were decreased, mean while parameter of VFA was increased at initially, the 20 day and 40 day. Quantitative analysis of the flammable biogas from some of the combination showed high methane contents. The Bg-25 had 75% CH4content, BNs-35 had 74% CH4 content and Bg-30 had 70 % CH4 content. The result of semi-continuos scale of 300 L digester showed that the optimal performance of bioreactor was feeding rate at 1,4 kg TS/L/day; 2,3 kg TS/L/day and  4,1 kg TS/L/day which resulted in biogas  64.4 L/ day with methane content is 70 %.Keywords: sugarcane bagasse, pineapple waste, biogas, methane